ANALISA RSM (RESPONSE SURFACE METHODOLOGY) DENGAN VARIASI WIRESPEED, INTERPULSE, DAN ARUS TERHADAP MATERIAL REMOVAL RATE DAN KEKASARAN PERMUKAAN PADA PROSES WIRE - EDM - Arif Efendi (ROTOR, 2019)
ABSTRACT In this era, the machining process has been very advanced wich is equipped with advanced technologies. The impact of the machining process used to develop and increase quality and quantity product produce. Machining process wire – EDM (Wire Cutting Electrical Discharge Machining) is one of the non – conventional machining process wich is commonly used in die – mold, disk brake, punch, and cutting tools. The speed of MRR (Material Removal Rate) and the smoothness of a surface has a very important role in a product wich concerns lubrication, wear, friction and resistance problems. Based on the problem, a study was research for find out what variables affetc the response variable. From the result of the study it is known that the current and interpulse affected the MRR, and the current, interpulse, and wirespeed also affect surface roughness. With the RSM (Response Surface Methode) methode optimum result for MRR the fasted 64,5688 mm3/minutes and the surface roughness smoothest 5,2391 µm with the combination variable current is 8 amp, interpulse, 7 µs, and wirespeed 5 mm/s. Keywords: Wire – EDM, Response Surface Methode (RSM), Material Removal Rate (MRR), surface roughness